Cloud algebra : an innovative approach for managing resources, services and big data on clouds - Ahad, Mohd Abdul (2022)
In the current era of technological advancements, cloud computing is considered as one of the most promising computing paradigms. It is cost-effective, energy efficient, scalable and is location independent. In simple terms, a cloud computing technology provides various computing tools, facilities and mechanisms as a service to the end user. A user can opt for using these services as a pay-per-use model. This technology is indeed highly cost-effective, environment friendly and is a preferred option for those who don?t want to spend much on infrastructures, platforms or physical space required for setting up the enterprise. Cloud computing technology provides services like Software-as-a-Service (SaaS), Platform-as-aService (PaaS), Infrastructure-as-a-Service (IaaS), Computing-as-a-Service (CaaS) etc. Recently a new service called DaaS (Data-as-a-Service) has also emerged in which data is provided as a service to the users. This paper proposes a concept of creating algebra for the cloud computing environment called as cloud algebra (CA). Using the proposed cloud algebra we can perform several basic mathematical functions like addition, deletion, union, intersection and other aggregate functions on clouds directly. This means that using the proposed cloud algebra, two or more clouds can be added. One cloud may be joined with other clouds and two or more clouds can be compared and so on. Furthermore, the data stored on the clouds can also be effectively and efficiently managed using the proposed cloud algebra. Along with the data, the cloud services and resources can also be managed in a much effective and efficient manner using the proposed cloud algebra.